Pengaruh Computer Anxiety dan Computer Attitude pada Minat Mahasiswa dalam Menggunakan Software Akuntansi - Dewi, Ni Komang Urip Krisna; Trisnadewi, Ni Ketut Sinta (Politeknik Raflesia Press, 2024)
This research aims to determine the factors influencing computer anxiety and computer attitude at student interest in using accounting software. This research uses quantitative methods. The population used in this research are university student major accounting at Politeknik Negeri Bali. The sample used in this research was 152 student. This research data was collected by distributing questionnaires directly to student. The analysis used in this research is multiple linear regression analysis with SPSS version 22 software tools. The results of this study show that computer anxiety does not affect accounting student’s interest in using accounting software and computer attitude has an affect accounting student’s interest in using accounting software.